HUBUNGAN ASUPAN ENERGI DAN PROTEIN, KUALITAS TIDUR DAN AKTIVITAS FISIK TERHADAP PRESTASI BELAJAR DI SMK TUNAS GRAFIKA INFORMATIKA 2020 - Dinda Anggita Mulia, (2021)
Academic peformance is one of indicators of adolascent's quality. Factors of academic peformance consist of internal and external factors. Adolescents's health is the most important internal factor was supported by a lifestyle including food intake, sleep patterns and physical activity. This study aims to analyze the relationship to energy and protein intake, sleep quality, and physical activity of SMK Tunas Grafika Informatika adolescent's. This was an observational study with a cross sectional approach. The population in this study were students of SMK Tunas Grafika Informatika with a total sample of 101 respondents. Respondents were randomly selected using Stratified Random Sampling method. The Dataa was collected using questionnaires and online interviews. Data was analized using Spearman Rank and Kendall's Tau b test. Based on statistical result, there was significant relationship between academic peformance with energy intake (P value = 0.012), protein intake (P value = 0,002), sleep quality (P value = 0.001), and physical activity (P value = 0.002). Academic peformance had positive correlation with energy intake with weak strength, protein intake with moderate strength, sleep quality with moderate strength and physical activity with weak strength. Key Word : Adolescent, Academic Peformance, Energy Intake, Protein Intake, Sleep Quality, Physical Activity